Photo-identification as a technique for recognition of individual fish: a test with the freshwater armored catfish Rineloricaria aequalicuspis Reis & Cardoso, 2001 (Siluriformes: Loricariidae) - Dala-Corte,Renato B. (2016)
Abstract Photo-identification allows individual recognition of animal species based on natural marks, being an alternative to other more stressful artificial tagging/marking techniques. An increasing number of studies with different animal groups has shown that photo-identification can successfully be used in several situations, but its feasibility to study freshwater fishes is yet to be explored. We demonstrate the potential use of photo-identification for intraspecific recognition of individuals in the stream-dwelling loricariid Rineloricaria aequalicuspis . We tested photo-identification in laboratory and field conditions based on the interindividual variability in abdominal bony plates. Our test yielded high correct matches in both laboratory (100%) and field conditions (> 97%), comparable to other reliable techniques and to studies that successfully used photo-identification in other animals. In field conditions, the number of correct matches did not differ statistically between computer-assisted and naked-eye identification. However, the average time expended to conclude computer-assisted photo evaluations was about half of the time expended to conclude naked-eye evaluations. This result may be exacerbated when using database with large number of images. Our results indicate that photo-identification can be a feasible alternative technique to study freshwater fish species, allowing for a wider use of mark-recapture in ecological and behavioral studies.